Hantavirus infection among children hospitalized for febrile illness suspected to be dengue in Barbados - Alok Kumar; Kandamaran Krishnamurthy; Anders L. Nielsen (Elsevier, 2016)
Summary: Emerging picture of hantavirus infection in the South America is characterized by greater proportion of childhood infection and wider spectrum of disease from mild asymptomatic to lethal cardiopulmonary disease. Barbados is endemic for dengue and leptospirosis, both of which share clinical features with hantavirus infection and in many cases neither of these diagnosis could be confirmed. We investigate whether some of the children hospitalized with suspected dengue could indeed have been hantavirus infections. In this prospective study children hospitalized with suspected dengue were tested for hantavirus infection using ELISA for the IgM antibodies. Thirty-eight children tested positive for hantavirus infection. They presented with fever, headache and mild respiratory and gastrointestinal symptoms and signs. None of them had features suggestive of hantavirus cardiopulmonary syndrome. Blood count values ranged from low to normal to high for their age. There were no deaths. Hantavirus infection is prevalent in this Caribbean country. It predominantly presents with milder disease and is responsible for some of the nonspecific febrile illnesses in children. Keywords: Hantavirus infection, Children, Caribbean, Clinical features